Relationship between perceived costs, perceived benefits and knowledge sharing behaviour among lecturers in educational institution in Malaysia - Abdul Hamid, Jamaliah; Sulaiman, Sarinah (Universiti Putra Malaysia Press, 2013)
Knowledge sharing behaviour has positive impact on individual innovation capability. However, since sharing knowledge is often unnatural, effective strategies and sufficient initiatives need to be deployed to ensure lecturers communicate their teaching experiences with others. This paper examines the extent of knowledge sharing amongst lecturers in an educational institution in Malaysia, and whether their knowledge sharing behaviour is influenced by their perceptions of costs-benefits in knowledge sharing. The analysis is based upon questionnaire surveys of lecturers (N=50) on their perception of costs and benefits motivation factors affecting their behaviour in sharing knowledge. While perceived benefits explained better orientation towards knowledge sharing, certain cost factors tended to restrict actual knowledge sharing. The article notes the influence of some perceived benefits dimensions in facilitating knowledge sharing behaviour in academic work setting. Recommendations on maximizing the influence of the related perceived benefits are also discussed.